Clinical Utility and Accuracy of UTI Calculator for Estimating the Probability of Urinary Tract Infection in Young Febrile Children - Asif Khan, Mohammad Rashidullah, Sami Ur Rahman, Noorshad Khan, Nizamudin, Mohib Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To investigate the accuracy of the UTI Calculator (UTI Calc) in predicting UTI in children by comparing the results of urine culture sensitivity tests (C/S). Study Design: Cross-sectional/descriptive study Place and Duration: The study was conducted at Urology Ward of Saidu Group of Teaching Hospitals, Swat during the period from 1st June 2020 to 31st December 2020. Methods: A total of eighty five children having ages from 4 to 24-months were presented. Children with fever >38oC were included. Following informed written agreement from the authorities, the demographics of enrolled cases were documented. Efficacy of UTI calculator was assessed in terms of diagnosing urinary tract infection among children. SPSS 21.0 was used to analyze complete data. Results: Among 85 cases, majority were male 50 (58.8%) infants and 35 (41.2%) were females. The mean age of the children was 8.44±7.65 years. Frequency of UTI was found among 9 (10.6%) febrile infants. Among 85 patients clinical UTI was high in 45 (52.9%) cases and by urine examination UTI found among 10 (10.6%) cases. Frequency of sensitivity was 100% and specificity 96%. E. coli was the predominant bacterium in 10 (11.8%) and urine cultures positive in (7.1%). Conclusion: In children, just a few clinical signs and symptoms are helpful in diagnosing or ruling out a urinary tract infection. Clinical prediction rules may be more accurate, but they need be externally verified. Urine collection should not be limited to children who have an unexplained fever or other symptoms that imply a urinary tract infection.